Tantangan dan Strategi Blended Learning Pada Mahasiswa Universitas Terbuka - Intan Amalia Putri; Fenny Trisnawati; Mujiono Mujiono (Annusfy : Journal of Multidisciplinary Research, 2026)
This research aims to identify the challenges faced by UT students in participating in blended learning and to explore the strategies used to overcome these challenges. The study employed a qualitative approach using a case study method. Data were collected through semi-structured interviews with seven active UT students who had experience in both online and face-to-face learning activities. The data were analyzed using thematic analysis based on the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that students encounter several major challenges, such as technical and internet connectivity problems, difficulties in accessing learning patforms, limited interactions, time management issues, and physical and mental fatigue, particularly among working students. To adress these challenges, students applied various adaptive strategies, including effective time management, anticipation of technical problems, improvement of self-regulated learnin, creation of a supportive learning environment, maintenance of physical and mental health, and strengthening of self-motivation. These findings suggest that the effectiveness of blended learning at Universitas Terbuka depends not only on institutional support and technological infrastructure but also on students learning readiness and adaptive strategies